Field notes contributed by Thomas J. Staudt, fall 1984 - Staudt, Thomas J.et al (1984)
Field notes were contributed by Thomas J. Staudt, fall 1984. An immature Northern Goshawk is described in detail. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed